Spectral components in electromyograms from four regions of the human masseter, in natural dentate and edentulous subjects with removable prostheses and implants - Guzmán-Venegas, Rodrigo A.; Palma, Felipe H.; Biotti P, Jorge L.; de la Rosa, Francisco J. Berral (Archives of oral biology, 2018)
•Spectral components of the masseter are different in anterior/posterior regions.•Spectral changes may be due to differences in fiber type distribution in edentulous.•Removable prostheses group showed greatest differences with natural dentate. To compare the frequency or spectral components between different regions of the superficial masseter in young natural dentate and total edentulous older adults rehabilitated with removable prostheses and fixed-implant support. A secondary objective was to compare these components between the three groups. 21 young natural dentate and 28 edentulous (14 with removable prostheses and 14 with fixed-implant support) were assessed. High-density surface electromyography (sEMG) was recorded in four portions of the superficial masseter during submaximal isometric bites. Spectral components were obtained through a spectral analysis of the sEMG signals. An analysis of mixed models was used to compare the spectral components. In all groups, the spectral components of the anterior portion were lower than in the posterior region (p < 0.05). Both edentulous groups showed lower spectral components and median frequency slope than the natural dentate group (p < 0.05). The removable prostheses group showed the greatest differences with natural dentate group. There were significant differences in the spectral components recorded in the different regions of the superficial masseter. The lower spectral components and fatigability of older adults rehabilitated with prostheses could be a cause of a greater loss of type II fibers, especially in the removable prostheses group.